Multilocus Sequencing of Corynebacterium pseudotuberculosis Biotype Ovis Strains. - Sellyei, Boglárka; Bányai, Krisztián; Bartha, Dániel; Hajtós, István; Fodor, László; Makrai, László (BioMed Research International, 2017)
Thirteen Corynebacterium pseudotuberculosis biotype ovis strains isolated from clinical cases of caseous lymphadenitis in Hungary were characterised using multilocus sequencing and their phylogenetic comparison was carried out on the basis of four housekeeping genes (groEL1, infB, dnaK, and leuA). The in silico analysis of the 16 frequently studied housekeeping genes showed that C. pseudotuberculosis strains could be readily distinguished from C. diphtheriae and C. ulcerans strains; however, sequences of the same genes in the two biotypes of the C. pseudotuberculosis were highly similar; the heterogeneity values were low. Genes dnaK, infB, groEL1, and leuA showed marked genetic variation within C. pseudotuberculosis, and strains of the two biotypes of C. pseudotuberculosis could be differentiated. Analysis of the individual genes showed a fairly conservative nature of C. pseudotuberculosis biotype ovis strains. The greatest genetic differentiation was seen in the dnaK and infB genes and concatenations of these two genes were very useful in the genetic separation of the studied strains.